1988
DOI: 10.1016/0309-1651(88)90128-2
|View full text |Cite
|
Sign up to set email alerts
|

Manganese inhibits benzoyl peroxide/copper-dependent lipid peroxidation in the microsomal fraction of rabbit dental pulp

Abstract: 1. Of all the cations tested only manganese ion inhibited the benzoyl peroxide/Cu2+-dependent formation of thiobarbituric acid (TBA)-reactive substance. 2. Ki of Mn2+ for the formation of TBA-reactive substance was 5.0 microM. 3. The inhibitory manner of manganese was non competitive against copper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In mammalian tissues, Mn 2+ inhibits iron-induced lipid peroxidation and dopamine depletion (Sziraki et al, 1995(Sziraki et al, , 1998. The reduction of copper-dependent low-density lipoprotein conjugation (Tsujimoto et al, 1988), and iron-induced phospholipid peroxidation, by Mn 2+ has also been demonstrated in mammalian cultured cells (Tampo and Yonaha, 1992).…”
Section: Introductionmentioning
confidence: 93%
“…In mammalian tissues, Mn 2+ inhibits iron-induced lipid peroxidation and dopamine depletion (Sziraki et al, 1995(Sziraki et al, , 1998. The reduction of copper-dependent low-density lipoprotein conjugation (Tsujimoto et al, 1988), and iron-induced phospholipid peroxidation, by Mn 2+ has also been demonstrated in mammalian cultured cells (Tampo and Yonaha, 1992).…”
Section: Introductionmentioning
confidence: 93%